2015
DOI: 10.1021/acs.jmedchem.5b00410
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Piperlongumine Analogues and Discovery of Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2) Activators as Potential Neuroprotective Agents

Abstract: The cellular antioxidant system plays key roles in blocking or retarding the pathogenesis of adult neurodegenerative disorders as elevated oxidative stress has been implicated in the pathophysiology of such diseases. Molecules with the ability in enhancing the antioxidant defense thus are promising candidates as neuroprotective agents. We reported herein the synthesis of piperlongumine analogues and evaluation of their cytoprotection against hydrogen peroxide- and 6-hydroxydopamine-induced neuronal cell oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 65 publications
4
93
0
Order By: Relevance
“…6-Hydroxydopamine (6-OHDA) is a well-established neurotoxin used to generate PD models in animals or cells. 45,46 We employed the 6-OHDA-treated PC 12 cells as a cellular model of PD 47–49 and applied Msr-blue to probe the function of Msrs in the cells. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6-Hydroxydopamine (6-OHDA) is a well-established neurotoxin used to generate PD models in animals or cells. 45,46 We employed the 6-OHDA-treated PC 12 cells as a cellular model of PD 47–49 and applied Msr-blue to probe the function of Msrs in the cells. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PCR primers specific to each gene are as follows: GAPDH: 5 0 -cagtgccagcctcgtctcat-3 0 and 5 0 -aggggccatccacagtcttc-3 0 ; heme oxygenase-1 (HO-1): 5 0 -gccctggaagaggagatagag-3 0 and 5 0 -tagtgctgtgtggctggtgt-3 0 ; NQO1: 5 0 -tcaccactctactttgctccaa-3 0 and 5 0 -ttttctgctcctcttgaacctc-3 0 ; Trx1: 5 0 -ccttctttcattccctctgtgac-3 0 and 5 0 -cccaaccttttgaccctttttat-3 0 ; TrxR1: 5 0 -actgctcaatccacaaacagc-3 0 and 5 0 -ccacggtctctaagccaatagt-3 0 . Target genes' expression was measured and normalized to the GAPDH expression level [34,40].…”
Section: Qrt-pcrmentioning
confidence: 99%
“…In the following activity evaluation, it was found that compound 7 promoted Nrf2 translocation into the nuclei and up-regulated the expression of c-GCS, NQO1, HO-1. These downstream proteins, NQO1, c-GCS and HO-1 29,30 Both in HCT116 and normal cells, 7 did not show cytotoxicity. What is more, it displayed cell protection in three normal cells such as L02, NCM460 and PC12 cells against H 2 O 2 damage.…”
Section: Discussionmentioning
confidence: 93%